THE EFFECT OF QUALITY TANGIBLES, RELIABILITY, RESPONSIVENESS, ASSURANCE, EMPATY ON PATIENT SATISFACTION AT QUEEN LATIFA GENERAL HOSPITAL - Purwanti, Siti; Sugiyanto, Bambang; Wening, Nur; Moertono, Bambang (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2019)
Background:Queen Latifa General Hospital is type D hospital that will be developed to be type C hospital. Thisdevelopment is done to further improve the service and claim value of BPJS to increase the welfareat Queen Latifa General Hospital, to fulfill the procurement of service facilities and to increase theconsumer satisfaction as well. It needs to do the research about how the level of patient satisfactiontowards the service of Queen Latifa General Hospital so that it is able to know about quality ofhospital service in order to be type C hospital in the future. Method:This research uses non-experimental quantitative design, with descriptive regression design, theresearch design used is cross sectional because the data collection of independent variables anddependent variable are done simultaneously at the same time, that is the quality of service towardsthe patient satisfaction at Queen Latifa General Hospital. Results and Discussion:From the results of F test in this study, it is obtained the F value is 12.32 with a significance number(P value) of 0.000. With 95% significance level, it means that variable of Tangibles, Reliability,Responsiveness, Assurance, Empathy have significant influence on patient satisfaction variable.The value of Adjusted R2 is 0.64 which means that the independent variable (Tangibles,Reliability, Responsiveness, Assurance, Empathy) can explain the dependent variable (Patientsatisfaction) of 64%, while the rest is explained by other factors which are not examined. Theresults of Multiple Regression Analysis Value of 0.29 on tangibles variable is positive, the valueof -0.24 in Reliability variable is negative, the value of -0.21 on responsiveness variable isnegative, the value of 0.64 on assurance variable is positive, and the value of 0.35 on the empathyvariable is positive, so that it can be concluded that the higher the quality of empathy, the higherthe patient satisfaction will be. Conclusion:The service quality at Queen Latifa General Hospital has been running well in terms of quality oftangibles, reliability, responsiveness, assurance, and empathy.